Contemporary Challenges to Nuclear Deterrence in South Asia - Zeeshan Hayat; Misbah Arif (CISS Insight Journal, 2024)
Pakistan’s nuclear weapons capability has played a crucial role in deterring India from waging war. Deterrence maintains a fragile stability because India is rapidly modernizing its military and is being propped up by the United States as the “net security provider” in the Asia Pacific region. These strategic developments are becoming a source of insecurity beyond South Asia. With added confidence, India has engaged in irresponsible behavior, such as surgical strikes and brinkmanship during crises. India has been signaling the resumption of nuclear testing, shedding ambiguity in its No First Use doctrine, and adopting a pre-emptive nuclear strike posture. The growing asymmetry in conventional and strategic domains is increasing instability in nuclear deterrence. These factors would increase Islamabad’s security dilemma. This study elaborates on the challenges Indian postures pose to stable deterrence in South Asia and measures the West, especially the United States, can take to avoid disturbing the region’s balance.